Handbook of global economic policy - Nagel, Stuart S., 1934- (Marcel Dekker, 2000)
A handbook of global economic policy. It develops practical, non-ideological solutions to the problems, and tests its solution's feasibility through economic, administrative, political, psychological, legal, international and technological obstacles.
Includes index.
Keywords: Economic policy -- Case studies.; Environmental policy -- Economic aspects -- Case studies.; Labor policy -- Case studies.; Full employment policies -- Case studies.; Industrial policy -- Case studies.; Post-communism -- Case studies.; Policy sciences -- Case studies.; Politique économique -- Études de cas.; Environnement -- Politique gouvernementale -- Aspect économique -- Études de cas.; Travail -- Politique gouvernementale -- Études de cas.; Plein emploi -- Études de cas.; Politique industrielle -- Études de cas.; Postcommunisme -- Études de cas.; Sciences de la politique -- Études de cas.; POLITICAL SCIENCE -- Public Policy -- Economic Policy.; BUSINESS & ECONOMICS -- Government & Business.; BUSINESS & ECONOMICS -- Development -- Economic Development.; BUSINESS & ECONOMICS -- Development -- Business Development.; BUSINESS & ECONOMICS -- Structural Adjustment.; BUSINESS & ECONOMICS -- Development -- General.; Economic policy; Environmental policy -- Economic aspects; Full employment policies; Industrial policy; Labor policy; Policy sciences; Post-communism; Electronic books.; Case studies; Case studies.; Études de cas.